(untitled) (Al-Aasar, 2025)
The Prophetic biography (Sīrah) of Prophet Muhammad ﷺ provides a comprehensive and practical framework for establishing social justice based on solidarity, equality, and economic fairness. This research examines the core dimensions of social solidarity (takāful) and equality (musāwāt) as demonstrated in the life and governance of the Prophet ﷺ, particularly within the socio-economic context of Madinah. It explores how the Prophet’s policies ensured equitable distribution of wealth, eradicated class-based discrimination, and promoted a welfare-based society grounded in ethical and spiritual values.The study highlights mechanisms such as zakat, voluntary charity (ṣadaqah), prohibition of usury (ribā), and the institution of waqf (endowments), which formed the economic backbone of the early Islamic state. These tools effectively addressed poverty, inequality, and economic exploitation, making the prophetic model a timeless reference for tackling modern economic challenges. Furthermore, the research draws parallels between the economic issues of the Prophet’s time and today’s crises such as global inequality, unemployment, inflation, and economic marginalization. It argues that reviving Prophetic principles can contribute significantly to formulating ethical and inclusive economic systems in the contemporary world. Through a critical and analytical reading of sīrah sources, this paper calls for a reintegration of Prophetic socio-economic ethics into modern policy frameworks. It concludes that the Prophetic model is not only historically relevant but also practically applicable in addressing the socio-economic needs of diverse, pluralistic societies today.